Dynamics of the Salatiga Islamic Movement in 2009-2019 : Pasang Surut Gerakan Islam Salatiga Tahun 2009-2019 - Apriliani, Luvita (Nur Science Institute, 2023)
This research focuses on the dynamics of PMII Cadreization of the Faculty of Syari'ah Rayon Zubair Umar Al-Jailani in 2009-2019. The focus of this research is limited to three problems, namely; (1) What is the historical background of the PMII IAIN Salatiga organization; (2) What was the initial period for the establishment of PMII of the Syari'ah Faculty; and (3) What are the Non-Academic Skill improvement programs for PMII organizational cadres, Faculty of Syari'ah Rayon Zubair Umar Al-Jailani in 2009-2019? This study uses historical research methods, namely heuristics, criticism, interpretation and historiography. The results of the study found that the cadre programs at PMII of the Faculty of Sharia experienced ups and downs according to the demands of the times. Several important findings in this study were cadre needs-based cadre programs such as strengthening non-academic skills, intellectual and social strengthening, and academic strengthening in order to erase the declining image of PMII cadres in the academic world.